2021
DOI: 10.1134/s0006297921060080
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Social Isolation Reduces Expression of the BDNF Precursor and Prolyl Endopeptidase in the Rat Brain

Abstract: Early-life stress is a risk factor for the development of behavioral and cognitive disorders in humans and animals. Such stressful situations include social isolation in early postnatal ontogenesis. Behavioral and cognitive impairments associated with neuroplastic changes in brain structures. We have found that after ten weeks of social isolation, male Wistar rats show behavioral abnormalities and cognitive deficit, accompanied by an increase in the relative expression of gene encoding serine protease prolyl e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Reported changes in BDNF expression are confounded by reduced environmental stimulation and social interactions experienced by the rhesus monkeys. Several studies have demonstrated stress-induced alterations in BDNF expression in various brain regions in rodents (111)(112)(113)(114)(115)(116). Moreover, BDNF mRNA and protein levels in several brain areas are increased following environmental enrichment (117)(118)(119).…”
Section: Discussionmentioning
confidence: 99%
“…Reported changes in BDNF expression are confounded by reduced environmental stimulation and social interactions experienced by the rhesus monkeys. Several studies have demonstrated stress-induced alterations in BDNF expression in various brain regions in rodents (111)(112)(113)(114)(115)(116). Moreover, BDNF mRNA and protein levels in several brain areas are increased following environmental enrichment (117)(118)(119).…”
Section: Discussionmentioning
confidence: 99%
“…This should generate deeper exploration into the inflammatory pathways but also promote investigation of additional important biomarkers associated with motor and cognitive function. Additionally, we plan to investigate how apathy may promote behaviors such as social isolation and decreased motor activity, which may promote inflammatory cytokines [ 59 , 60 , 61 , 62 , 63 , 64 ] and decrease brain-derived neurotrophic factor [ 65 , 66 , 67 , 68 , 69 ]. Another mechanism that warrants further exploration is the relationship between blood–brain barrier (BBB) disruption, which can occur in normal aging, and disease states including cerebrovascular disease and metabolic syndrome [ 70 , 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%